Feasibility Study Pembangunan Technopark di Kabupaten Toba - Mutiara Zallya Rizkita; Palti Marulita Sitorus; Khairunnisa Khairunnisa; Andry Alamsyah; Maman Abdurohman (Departement of Mathematics Education, 2023)
Science and Technology Parks (also known as technoparks) are centers for the efficient and effective sharing of knowledge and resources across various sectors of society, including business, academia, government, and the nonprofit sector. The purpose of this study is to answer the formulation of the problem, namely the Feasibility Study in Technopark Development in Toba Regency. The research method used is qualitative research. Using literature review studies by looking for secondary sources of information, such as previous research, data from affiliated organizations, local village records, and so on. The results of the study show that within 10 years, the NPV is IDR 679,597,945 with income increasing every year until the fifth year, because the NPV value is positive, the NPV is acceptable and the PP calculation itself is for 5.5 years. The conclusion obtained from the Technopark development in Toba Regency can be said to be feasible and with the existence of this Technopark it can be a breakthrough in business.